Shopping center and shopping mall: issues and failures of Victor Gruen’s design for the city of the twentieth century - Catherine Maumi (Belgeo)
The aim of this paper is to put Victor Gruen’s thinking into context, clarifying what he meant by ‘shopping center’ and ‘shopping mall’. It also seeks to understand the nature of the difficulties Gruen encountered when he tried to transpose his ideas onto European soil, particularly in France. The exchanges between Gruen and his European clients, partners and friends reveal a gap in expectations that is worth observing. While Gruen’s clients solicited him for his expertise on shopping centers, his main concern was that European countries did not follow the same path as the United States, where downtowns had been ruined by the policy of promoting suburbanization and the development of shopping centers. It is also interesting to analyze the discrepancy between Gruen’s practice and his increasingly critical attitude towards the solutions he had devised.